واقع استخدام مهارات الاتصال الصفي الفعّال لدى مدرّسي اللغة العربية - المحمد, أحمد (جامعة الوادي - University of Eloued, 2022)
هدف البحث إلى تعّرف واقع استخدام مهارات الاتصال الصفي الفعّال لدى مدرّسي اللغة العربية في مرحلة التعليم الثانوي العام (من وجهة نظرهم)، وإيجاد فروق امتلاك هذه المهارات تبعاً لمتغيرات عديدة، وتكوَّنت عينة البحث من (95) مدرساً ومدّرسة. اتبع الباحث المنهج الوصفي، وصمَّم استبانة مكوَّنة من (36) بنداً كأداة لتحقيق أهداف البحث. وأظهرت النتائج: - يوجد درجة تقدير (كبيرة) في درجة استخدام مهارات الاتصال الصفي على الدرجة الكلية والمحاور. - يوجد فرق ذو دلالة إحصائية بين متوسطي درجات المدرسين تُعزى إلى متغيرات: (الجنس - المؤهل العلمي - سنوات الخبرة) على الدرجة الكلية وبعض المحاور وذلك لصالح المتغيرات الآتية على التوالي: (الإناث - دبلوم فما فوق - المدرسين ذوي الخبرة الأعلى). Abstract: The research aimed at identify the reality of using effective classroom communication skills among teachers of Arabic in the general secondary education stage from their the Point of View, and the And find the differences in owning these skills according to many variables, and Research sample included (95) teachers. researcher adopted the descriptive analytical method, and he designed a questionnaire consisting of (36) items as a tool to achieve the objectives of the research. The results showed: -There is a (large) degree of appreciation in the degree of using effective classroom communication skills on the total score and axes. There is a statistically significant difference between the average grades of teachers due to the variables: (gender - academic qualification - years of experience) on the total degree and some axes, in favor of the following variables, respectively: (females - diploma and above - teachers with higher experience).
في مرحلة التعليم الثانوي العام
مقال
Keywords: مهارات الاتصال الصفي الفعّال، مدّرسي اللغة العربية; Effective Classroom Communication Skills, Arabic Language Teachers